Phonological Processes in Chagga Nativized Lex-emes Borrowed From Standard Swahili: A Chagga - English Comparative Study - Mallya, Gerald John (Indonesian Journal of English Language Studies (IJELS), 2018)
Linguistics as a present study, acts as an instrument towards promoting local languages. This recent study aims at studying some of phonological processes in Chagga language (Particularly Kibosho and Marangu varieties). Chagga is a Bantu language family spoken by Chagga people of Tanzania, south of Mount Kilimanjaro. Borrowing is the act of taking a word or a phrase from one language and used it in another language. The present study is carried out under Generative CV Phonology Theory, developed by linguists, Keyser and Clements in (1983). This theory strives to guide the present study on scrutinize phonological processes with their rules in Kibosho and Marangu varieties. The very study is the phonological type of study which employs qualitative method. The study employs Interview to observe the pronunciation by native speakers, voice note as linguistic variable need for homogenous resemblance of the uttered lexical items and the phonological processes. To answer study question one the study observes there are three major causes of phonological processes in Chagga as in English with very little variations namely: Phonological processes motivated by syllable structure rules [vowel insertion/ epenthesis], Phonological processes in Chagga language affecting syllable [consonant deletion] and Phonological processes motivated by phonemic reasons [cluster tolerance, feature change]. In adhering problem two the study has found similar phonological processes between English and Chagga with very little differences especially on phonemes which undergo the changes hence advocates for further analyses in local African and Asian languages to pursue a similar study or any nearly phonological study in order to preserve and promote local linguistics contents from ones native language.Keywords: Phonological processes, Nativazation, Phonological rules, Chagga languageI